The NHS Health Check programme: implementation in east London 2009-2011 - Robson, J; Dostal, I; Madurasinghe, V; Sheikh, A; Hull, S; Boomla, K; Page, H; Griffiths, C; Eldridge, S (BMJ Publishing Group, 2015)
Objectives: To describe implementation and results from the National Health Service (NHS) Health Check programme. Design: Three-year observational open cohort study: 2009–2011. Participants: People of age 40–74 years eligible for an NHS Health Check. Setting: 139/143 general practices in three east London primary care trusts (PCTs) serving an ethnically diverse and socially disadvantaged population. Method: Implementation was supported with education, IT support and performance reports. Tower Hamlets PCT additionally used managed practice networks and prior-stratification to call people at higher cardiovascular (CVD) risk first. Main outcomes measures: Attendance, proportion of high-risk population on statins and comorbidities identified. Results: Coverage 2009, 2010, 2011 was 33.9% (31 878/10 805), 60.6% (30 757/18 652) and 73.4% (21 194/28 890), respectively. Older people were more likely to attend than younger people. Attendance was similar across deprivation quintiles and was in accordance with population distributions of black African/Caribbean, South Asian and White ethnic groups. 1 in 10 attendees were at high-CVD risk (20% or more 10-year risk). In the two PCTs stratifying risk, 14.3% and 9.4% of attendees were at high-CVD risk compared to 8.6% in the PCT using an unselected invitation strategy. Statin prescription to people at high-CVD risk was higher in Tower Hamlets 48.9%, than in City and Hackney 23.1% or Newham 20.2%. In the 6 months following an NHS Health Check, 1349 new cases of hypertension, 638 new cases of diabetes and 89 new cases of chronic kidney disease (CKD) were diagnosed. This represents 1 new case of hypertension per 38 Checks, 1 new case of diabetes per 80 Checks and 1 new case of CKD per 568 Checks. Conclusions: Implementation of the NHS Health Check programme in these localities demonstrates limited success. Coverage and treatment of those at high-CVD risk could be improved. Targeting invitations to people at high-CVD risk and managed practice networks in Tower Hamlets improved performance.